Arduino automatic door opening system / Muhammad Afiq Ismail and Muhammad Fauzi Marzukhi - Ismail, Muhammad Afiq; Marzukhi, Muhammad Fauzi (2015)
This is an Electronics Project on Automatic Door Opening System Using IR Sensors which is used to automate door opening. This project will contribute a lot of pleasure in our daily life. For those disability and older people, they will appreciate the automatic door systems. This project also conserve energy from heating and air conditioning that would have been required otherwise. Thus, it saving-up on electricity costs. This project consist the infrared that can detect human motion to go through the door. The infrared signal will send to the micro controller. Then the micro controller send the signal to the stepper motor as in which the door is opened. After a few seconds, the door will close automatically if no more obstacle to be detected by the infrared sensor. This automatic door system is powered by using electricity to open and close the door